Analisa Penetapan Evaluasi Generalized System of Preference (GSP) Amerika Serikat Terhadap Indonesia dan Pengaruhnya Terhadap Kesepakatan Perdagangan Dibawah World Trade Organization (WTO) - Jeihan, Jodie; Loijens, Tasya Ester; Ekaningtyas, Intan (Jurnal Hukum Lex Generalis, 2020)
Liberalism is a basic principle adhered to by the United States in all its policies, including trade policies. This principle is also carried out by the President of the United States, Donald Trump, in the form of orientation towards bilateral agreements. When viewed from the trade relationship between Indonesia and the United States, the Generalized System of Preference or GSP facility is the only bilateral relationship that Indonesia can carry out with the United States. GSP is the US policy in the form of exemption from import duty on imports of certain goods from developing countries, in which case Indonesia is one of them. However, it turns out that there is a policy to evaluate the implementation of the GSP for Indonesia looking at the trade balance and Indonesian economic policies that have an impact on the United States. This evaluation has the potential to reduce Indonesia's Bargaining Position in the GSP facility. If this unexpected condition arrives, it could be detrimental to Indonesia because of the increase in tariffs imposed on the export sector. The author intends to examine the reevaluation policy in terms of international law.